2014
DOI: 10.1039/c4ra06248e
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants, viscosity and response time in nematic liquid crystals doped with ferroelectric nanoparticles

Abstract: We report on the role of ferroelectricity on the physical and electro-optic parameters in suspensions of nanoparticles in cyclohexane based, fluorinated nematic liquid crystals. The dielectric and elastic constants, response time, and viscosity of the suspensions were analyzed experimentally and compared with the undoped samples. Our study shows a decrease in the splay elastic constant and an increase in the dielectric constants, together with an increase in the average rotational viscosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…Based on the same analogy, the NLC molecular alignment in the vicinity of the nanoparticles will be controlled by the characteristics of the nanoparticles, such that the NLC will tend to align parallel to the surface normal of each nanoparticle rather than along the surface, as illustrated in Figure 7a. This proposed alignment is similar to that reported for colloidal systems and/or ferroelectric nanoparticles [5][6][7][8][9][10][11][12][13][14]. Here, we can compare the effects of doping with the two sizes of nanoparticles: R-812 (7 nm) and RX-50 (40 nm).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the same analogy, the NLC molecular alignment in the vicinity of the nanoparticles will be controlled by the characteristics of the nanoparticles, such that the NLC will tend to align parallel to the surface normal of each nanoparticle rather than along the surface, as illustrated in Figure 7a. This proposed alignment is similar to that reported for colloidal systems and/or ferroelectric nanoparticles [5][6][7][8][9][10][11][12][13][14]. Here, we can compare the effects of doping with the two sizes of nanoparticles: R-812 (7 nm) and RX-50 (40 nm).…”
Section: Resultssupporting
confidence: 86%
“…More recently, ferroelectric nanoparticles have attracted significant attention with regard to controlling the responses of NLC molecules. The ferroelectric nature of these nanoparticles can greatly enhance the physical and electro-optic properties of the host LC, including its phase transition temperature, dielectric and optical anisotropy, and Fréedericksz transition [9][10][11][12][13][14]. In a ferroelectric nanoparticle-doped system, the nanoparticles behave as molecular dipoles and can therefore affect the resulting LC order.…”
Section: Introductionmentioning
confidence: 99%
“…6,[14][15][16][17][18][19][20][21][22] In addition to the size, the nanoparticle surface properties are also crucial for the manifestation of a well dispersed medium. Surface modification of NPs has been mainly been employed to achieve long-term stability of NPs in the LC medium and to smoothen director distortions around NPs, 23 thus reducing the cost of elastic energy.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…Nina Podoliak et al investigated the impact of ferroelectric nanoparticles on the basic parameters of LCs using two different nematic LCs, TL205 and 18523 [50]. The dielectric constant measurements and electro-optic study showed that the ferroelectric nanoparticle doping causes a significant increase of the dielectric anisotropy and also reduces the splay elastic constants.…”
Section: Properties Of Doped Nematic Liquid Crystalsmentioning
confidence: 99%